ESSENCE OF COGNITIVE INDEPENDENCE AS AN IMPORTANT INDICATOR CREATIVE PERSON - N.I. Zelenkova (Academy of Cognitive and Natural Sciences, 2007)
The conditions of educational process, the conditions of its organization forms methods which help to debebop the Creative qualities of a person a covered in the article.